The Effect of Aviation Security Services on Passenger Satisfaction at Aji Pangeran Tumenggung Pranoto Samarinda Airport - Mutiara Handayani Aritonang (PT FORMOSA CENDEKIA GLOBAL, 2022)
Aviation Security (AVSEC) services at Aji Pangeran Tumenggung Pranoto Samarinda Airport are very important as aviation security personnel who have (mandatory) a license or certificate. a certificate of proficiency for officers (STKP) who are given duties and responsibilities in the field of Aviation Security. Based on the background and problem formulation, the purpose of this study is to 1) determine the effect of Aviation Security officer services on passenger satisfaction at Aji Pangeran Tumenggung Pranoto Samarinda Airport 2) find out how much influence the Aviation Security officer service has on passenger satisfaction at Aji Pangeran Tumenggung Pranoto Samarinda Airport. The data used in this study is primary data, namely data collected by distributing questionnaires or questionnaires directly to 100 respondents or airport service users at Aji Pangeran Tumenggung Pranoto Samarinda Airport researchers used quantitative research and analyzed using SPSS 23.0. After the questionnaires were distributed to 100 respondents, the data obtained were tested for validity, simple linear regression test, T test and coefficient of determination test. The results showed that there was a significant influence between the services of Aviation Security officers on passenger satisfaction at Aji Pangeran Tumenggung Pranoto Samarinda Airport. This is evidenced by the value of T arithmetic 17.744 > T table 1.98447. Based on the results obtained, the coefficient of determination (R Square) is 0.763 or 76.3%, meaning that there is 76.3% of the effect of service on passenger satisfaction, while the remaining 23.7% is influenced by other variables not tested in this study.